Globalization and Modernity—A Case Study of Cognac Consumption in Hong Kong - Smart, Josephine (Anthropologica, 2022)
Hong Kong is one of the top consumers of cognac. Yet the Chinese population in Hong Kong is extremely light in their drinking habits with less than 4% of the population described as regular drinkers. This paradox of light alcohol consumption habit and high level of actual consumption of cognac can be explained by the successful integration of cognac as the liquor of choice at wedding banquets since the 1970s, and a common item in gift exchange at important calendar and social occasions. The successful marketing of cognac in Hong Kong is shown to be closely linked to local economic conditions, symbolism and culturally appropriate conspicuous consumption. While the success of cognac in Hong Kong is an example of effective global circulation of goods, it also serves as an illustration of the resilience of cultural diversity within an increasingly integrated global economy. The consumption formats and meanings associated with cognac have been given "local colours" in Hong Kong.